Occurrence of microplastic in livestock and poultry manure in South China - Wu, Rui-Ting; Cai, Ying-Feng; Chen, Ying-Xi; Yang, Yi-Wen; Xing, Si-Cheng; Liao, Xin-Di (Environmental pollution (1987), 2021)
Microplastic (MP) contamination in soil has attracted much attention, and increasing evidence suggests that MPs can accumulate in agricultural soils through fertilization by compost. In addition, the most common raw materials for composting are livestock and poultry manure wastes. Because the presence of MPs may threaten the safe utilization of fertilizers composted by livestock and poultry wastes during crop planting, it is necessary to understand the contamination risk of MPs present in livestock and poultry manure. In this study, the distribution of MPs in 19 livestock and poultry farms with 3 different species was investigated by using FTIR microscopy. A total of 115 items manure MPs and 18 items feed MPs were identified as PP and PE types dominated by colorful fragments and fibers. Furthermore, after comparing the compositions of plastic products used in the feeding process, we proposed two transport pathways for MP pollution in manure and one potential transport pathway in feeds. Our result proved that the application of swine and poultry manure directly could be a new route of MPs in agricultural soil, furthermore, the presence of MPs could threaten the safety of resource utilization in agricultural soil by using swine and poultry manure for manure potentially. Not, only that, our study also provided a reference for the remediation of MP-contaminated soil. [Display omitted] •Severe microplastic contamination occurred in livestock and poultry farms.•Polypropylene, polyethylene, and polyester resin were the representative types.•Fibers and fragments are the predominant shapes with various colors.•Application of animal manure directly could be a route of MPs in agricultural soil.